Discovering Transcriptional Regulatory Elements From Run‐On and Sequencing Data Using the Web‐Based dREG Gateway. Issue 1 (27th December 2018) - Chu, Tinyi; Wang, Zhong; Chou, Shao‐Pei; Danko, Charles G.
Abstract: Transcription is a chromatin mark that can be used effectively to identify the location of active enhancers and promoters, collectively known as transcriptional regulatory elements (TREs). We recently introduced dREG, a tool for the identification of TREs using run‐on and sequencing (RO‐seq) assays, including global run‐on and sequencing (GRO‐seq), precision run‐on and sequencing (PRO‐seq), and chromatin run‐on and sequencing (ChRO‐seq). In this protocol, we present step‐by‐step instructions for running dREG on an arbitrary run‐on and sequencing dataset. Users provide dREG with bigWig files (in which each read is represented by a single base) representing the location of RNA polymerase in a cell or tissue sample of interest, and dREG returns a list of genomic regions that are predicted to be active TREs. Finally, we demonstrate the use of dREG regions in discovering transcription factors controlling response to a stimulus and predicting their target genes. Together, this protocol provides detailed instructions for running dREG on arbitrary run‐on and sequencing data. © 2018 by John Wiley & Sons, Inc.